Autotaxin-lysophosphatidic acid receptor signalling regulates hepatitis C virus replication - Farquhar, Michelle J.; Rössler, Stephanie (Journal of hepatology, 2017)
BACKGROUND & AIMS: Chronic hepatitis C is a global health problem with an estimated 170 million hepatitis C virus (HCV) infected individuals at risk of progressive liver disease and hepatocellular carcinoma (HCC). Autotaxin (ATX, gene name: ENPP2) is a phospholipase with diverse roles in the physiological and pathological processes including inflammation and oncogenesis. Clinical studies have reported increased ATX expression in chronic hepatitis C, however, the pathways regulating ATX and its role in the viral life cycle are not well understood. METHODS: In vitro hepatocyte and ex vivo liver culture systems along with chimeric humanized liver mice and HCC tissue enabled us to assess the interplay between ATX and the HCV life cycle. RESULTS: HCV infection increased hepatocellular ATX RNA and protein expression. HCV infection stabilizes hypoxia inducible factors (HIFs) and we investigated a role for these transcription factors to regulate ATX. In vitro studies show that low oxygen increases hepatocellular ATX expression and transcriptome analysis showed a positive correlation between ATX mRNA levels and hypoxia gene score in HCC tumour tissue associated with HCV and other aetiologies. Importantly, inhibiting ATX-lysophosphatidic acid (LPA) signalling reduced HCV replication, demonstrating a positive role for this phospholipase in the viral life cycle. LPA activates phosphoinositide-3-kinase that stabilizes HIF-1α and inhibiting the HIF signalling pathway abrogates the pro-viral activity of LPA. CONCLUSIONS: Our data support a model where HCV infection increases ATX expression which supports viral replication and HCC progression. LAY SUMMARY: Chronic hepatitis C is a global health problem with infected individuals at risk of developing liver disease that can progress to hepatocellular carcinoma. Autotaxin generates the biologically active lipid lysophosphatidic acid that has been reported to play a tumorigenic role in a wide number of cancers. In this study we show that hepatitis C virus infection increases autotaxin expression via hypoxia inducible transcription factor and provides an environment in the liver that promotes fibrosis and liver injury. Importantly, we show a new role for lysophosphatidic acid in positively regulating hepatitis C virus replication.
Gesehen am 26.10.2018